Macrophage polarization: molecular mechanisms, disease implications, and targeted therapeutic strategies - Ji, Yanan; Li, Xia; Yao, Xinlei; Sun, Jiacheng; Yi, Jia; Shen, Yuntian; Chen, Bingqian; Sun, Hualin (Frontiers in Immunology, 2025)
Macrophage polarization represents a fundamental plasticity process within innate immunity, profoundly influencing tissue homeostasis and disease progression. Based on developmental origins, macrophages are categorized into tissue-resident macrophages and monocyte-derived macrophages, which collectively form a dynamic host defense network. Notably, the functional states of macrophages exist along a continuum, extending beyond the classical pro-inflammatory (M1) and anti-inflammatory/reparative (M2) dichotomy. These states are dynamically shaped by spatiotemporally heterogeneous microenvironmental signals and coordinated through intricate molecular networks. Key signaling pathways guide polarization directions. Metabolic reprogramming, where M1 polarization relies on glycolysis and the pentose phosphate pathway while M2 polarization favors oxidative phosphorylation and fatty acid oxidation, not only supplies energy but also generates regulatory metabolites. Furthermore, epigenetic mechanisms, including DNA methylation, histone modifications, and non-coding RNAs, contribute to stabilizing polarized phenotypes. These mechanisms are interconnected, forming feedback loops that collectively sculpt macrophage functional diversity. Dysregulated polarization underlies numerous diseases. In response, therapeutic strategies targeting macrophage polarization are rapidly emerging. These include pharmacological interventions using small molecules and metabolic modulators to reprogram cell phenotypes, immunotherapies such as CAR-M macrophages or exosome-mediated reprogramming to remodel immune microenvironments, and precision regulation through gene editing or epigenetic modifications. Although innovations like single-cell omics, spatial transcriptomics, computational modeling, and synthetic biology are advancing the field, clinical translation still faces challenges including off-target effects, inefficient delivery, microenvironmental dependency. Future research must integrate multi-omics data to develop individualized therapies, further investigate the stability and plasticity of polarization states, and leverage smart materials and advanced model systems to advance precision immunotherapeutics.